DESENVOLVIMENTO DE BASES ATÔMICAS ADAPTADAS PELO MÉTODO DA COORDENADA GERADORA HARTREE-FOCK (MCG-HF) MODIFICADO, PARA OS ELEMENTOS DO QUARTO PERÍODO DA TABELA PERIÓDICA, E APLICAÇÃO EM CÁLCULOS DE PROPRIEDADES DE MOLÉCULAS E ÍONS - Rodrigues, Mauricio Gustavo (2012)
How the better choice to combine theoretical and experimental works? Using the higger possible number of particles, after an experimental works with system in solution, and this presents many particles. But, for a good description of any sistem, it requires a deeper level of theory. The miscellany of these two questions is the main objectiv of the current computional chemists. Thus, attempts are increasingly the basis sets smaller and simultaneously more accurate, so that they give good results and does not have computational cost. Using the Generator Coordinate Hartree-Fock method, this work genetares atomic basis sets for the atoms of fourth row of the periodic table, so that basis set can compete with Dunning, Pople and ECP basis set. The results presented demonstred atomic values important, provided thar prevents the variational principle to obtain better results that the result obtained by Numerial Hartree-Fock. In the application of molecular system, it is used as the basis of Dunning pattern, since they are not applicable in large systems. Thus, the calculations shown in this work that this new methodology is powerful and can cope with the basis set already published.